Knowledge and Emotions in Cross-Racial Dialogues: Challenges and Opportunities for Adult Educators Committed to Racial Justice in Educational Settings. (August 2014) - Manglitz, Elaine; Guy, Talmadge C.; Merriweather, Lisa R.
Our society reflects a kaleidoscope of differences in terms of race, ethnicity, class, religion, and gender identity. These differences are evident from the boardroom to the classroom in higher education and can result in impaired communication when race is the topic of discussion. To effectively facilitate race-based dialogues, adult educators must deliberately and intentionally build their cognitive and emotive capacity. Capacity building involves adult educators acknowledging their privilege and systems of advantage, attaining cultural knowledge, taking emotional risks, and developing the ability to better organize formal learning and capitalize on informal learning opportunities, to engage in more genuine and appropriate racial dialogues. As we are ushered through the 21st century, issues of race and racism will remain as salient as ever as long as the disturbing silence, surrounding them in our work and school spaces, is allowed to persist. Considerations for the development of cognitive and emotive capacities are described to assist adult educators in contributing to a more just society.